PENGARUH FAKTOR-FAKTOR TOTAL QUALITY MANAGEMENT TERHADAP TINGKAT KEPUASAN PESERTA DIDIK DAN ALUMNI - LUSSY WIDIA ASMARANINGTYAS (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2021)
This study aims to examine how the Influence of Total Quality Management (TQM) Factors on Student and Alumni Satisfaction Levels by using Student Advisors and Soft Skill Training as Intervening Variables at Lp3i Sidoarjo. The total population of students is 278 people and the total population of alumni for the 2-year professional program is 215 people. The sample used for this study was 160 students and 136 alumni and the results were processed using a simple linear regression analysis tool with the help of SPSS 21.0 for windows. The results of the study indicate that the significance value is 0.000 <0.050 and has a t value (F-count) of 39.885 which is greater than t (F-table) of 2.305. This means that there is a significant joint influence between the Quality of Educational Institutions (X1), Focus on Students (X2), Human Resource Management (X3), Leadership (X4), Continuous Improvement (X5) on Student and Alumni Satisfaction (Y ) So that the hypothesis stating that it is suspected that the factors of Total Quality Management (TQM) in the form of the dimensions of the quality of educational institutions, focus on students, human resource management, leadership and continuous improvement affect the level of satisfaction of students and alumni at the Institute of Education and Professional Development. Indonesia (LP3I) Sidoarjo proved correct. Further results show that the influence (linear relationship) between Student Advisor and Soft Skill Training (Z) on Student Satisfaction and Alumni (Y) shows the magnitude of the influence of Student Advisor and Soft Skill Training (Z) variables on Student and Alumni Satisfaction (Y) of 0.722 or 72.2% or considered significant. This is reflected in the significant figure of the variable (Z) to the variable (Y) of 0.000 which is smaller than 0.05. So that the hypothesis which states that the Total Quality Management (TQM) factors that influence student satisfaction, and (influenced) intervention by the variable role of student advisor and soft skill training at the Indonesian Institute of Education and Professional Development (LP3i) Sidoarjo, are proven to be true.